Penerapan Metode Tegatour (Teams-Games-Tournament) untuk Meningkatkan Sosial Anak Usia 5-6 Tahun - Baik Nilawati Astini; Ika Rachmayani; Nurhasanah Nurhasanah; Meri Apriani (Indonesian Publication Center, 2021)
The social development of children at birth in KB Habibi NW aok Tawah is still an immature and less cooperative child in play, unable to obey the rules and be responsible for his behavior. This is because the teacher’s induced social development stimulation is not optimal in which researcher are providing social stimulation to leaners by using established methods designed to fit the range of 5-6 yeas social development. The purpose of this study is to improve social skills through the Tegatour method for children aged 5-6 years at KB Darul Habibi NW Paok Tawah, Praya District, for the 2020/2021 academic year. The research was conducted using R&D development research with 3 stages of development, namely planning, implementation, observation and reflection on 10 children. data collection in this study using observation and documentation methods and data collection using qualitative descriptive. In the first stage of development research, the average result was 42.03% with the undeveloped category while in the second development stage it increased with an average value of 63.95% with the category starting to develop and in the third development stage the average value of children's social improvement increased to 80.03% with the criteria of developing as expected. Based on the results of this study, it can be concluded that the activities of the Tegatour method can improve the social skills of children aged 5-6 years in KB Darul Habibi NW Paok Tawah, Praya District, for the 2020/2021 academic year.